THE FUTURE OF HOLISTIC HEALTHCARE: TRANSFORMATIVE IMPACTS ON PROFESSIONALS AND LEARNING MODELS - Halvorsen, Magnus Erik; Bennett, Fiona Claire (International Research Journal Diagnostics, 2024)
In the dynamic landscape of healthcare sciences, the interpretation and significance of fundamental concepts like "holism" continually evolve in response to medical advancements, technological progress, socioeconomic shifts, and political changes. This evolution represents a continuous process of conceptual refinement driven by the practical application of the concept in clinical settings, ongoing scientific research that shapes empirical and conceptual theories, and the collective knowledge acquisition in educational institutions and informative gatherings like seminars and conferences. The contemporary healthcare paradigm is witnessing a transformation in the concept of holism. The holistic approach now encompasses a vast healthcare ecosystem, comprising professionals with distinct functions, roles, and responsibilities that necessitate interconnected communication across various organizational units and levels. Achieving unity, consistency, and harmonious care delivery and evaluation hinges on establishing a shared foundation for conceptual communication. Each healthcare discipline possesses its unique vocabulary and conceptual framework, shaped by the particular interests, focus areas, and contextual realities of the discipline. This diversity in language and terminology reflects the multidisciplinary nature of modern healthcare.